2018
DOI: 10.1002/admi.201800177
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Self‐Healing Fiber‐Reinforced Polymer Composites

Abstract: With the potential for small-scale damage to grow or coalesce under subsequent loading, FRP structures incorporate high safety factors to account for this defect sensitivity to ensure they will remain load bearing throughout their service life. This paradigm has resulted in many research groups worldwide exploring and developing the concept of self-healing or selfrepair being applied to FRPs, with the aim of achieving autonomous structural recovery via an embedded functionality, to address damage formation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 106 publications
0
65
0
Order By: Relevance
“…The processability of this PU SMP formulation enables its straightforward reconfiguration into numerous form factors, which, at the time opened up new opportunities for SMPs 341,342. Today, countless reports detail the integration of SMPs of a range of compositions and network chemistries into end uses spanning from deployable space structures343–345 to medical implants346–349…”
Section: Shape Memory Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The processability of this PU SMP formulation enables its straightforward reconfiguration into numerous form factors, which, at the time opened up new opportunities for SMPs 341,342. Today, countless reports detail the integration of SMPs of a range of compositions and network chemistries into end uses spanning from deployable space structures343–345 to medical implants346–349…”
Section: Shape Memory Polymersmentioning
confidence: 99%
“…While SMPs are not competitive with the energy densities achievable with SMA actuators, these materials have other distinct attributes: compositional variation, processability, and morphological diversity that differentiate their use and motivate integration in robotic devices. Foremost of these benefits is the considerable weight savings associated with the density of SMPs (polyurethanes—1.25 g cm ‐3 ) when compared to SMAs (Nitinol—6.4 g cm ‐3 ) 349,351. Another key advantage of SMPs in robotics is their tolerance of large deformations during shape memory cycling.…”
Section: Shape Memory Polymersmentioning
confidence: 99%
“…Collage of self‐healing materials addressed in the current Special Issue. Reproduced with permission …”
Section: Individual Contributions To the Special Issuementioning
confidence: 99%
“…Meanwhile, some other literatures also reported that the G IC , G IIC , ILSS, and flexural strengths of the FRPs can be improved by 98-150%, [16,17] 30-200%, [16,17] 10-69%, [18][19][20][21] and 8-26%, [22][23][24][25] respectively, by incorporating with CNTs-based resin films or coating interleaves. Obviously, previous studies have already demonstrated that the CNTBP-based interleaf shows significant reinforcing effect on the interlaminar performance of the FRPs, but these researches are usually carried out at room temperature and how the CNTBP affects the mechanical properties under low temperature is rarely considered.Due to the high strength, rigidity, thermal conductivity, and corrosion resistance, carbon FRPs (CFRPs) are increasingly utilized in high-tech engineering applications, such as airframes, space shuttles, satellites, cryogenic fuel tanks, [26,27] in which, some CFRP structures would undergo low-temperature environments such as ranging from 0 to −60 °C (e.g., airframes), and others might be exposed to cryogenic environment such as reaching −250 °C (e.g., liquid hydrogen tank). [28] On the Carbon Nanotubes This study introduces carbon nanotube buckypaper (CNTBP) into the easily fractured sites of [0°] 16 and [0°/90°] 4S composite laminates, and comparatively explores how the CNTBP affects the flexural properties of the laminates at 25, −15, and −55 °C.…”
mentioning
confidence: 99%
“…Due to the high strength, rigidity, thermal conductivity, and corrosion resistance, carbon FRPs (CFRPs) are increasingly utilized in high-tech engineering applications, such as airframes, space shuttles, satellites, cryogenic fuel tanks, [26,27] in which, some CFRP structures would undergo low-temperature environments such as ranging from 0 to −60 °C (e.g., airframes), and others might be exposed to cryogenic environment such as reaching −250 °C (e.g., liquid hydrogen tank). [28] On the Carbon Nanotubes This study introduces carbon nanotube buckypaper (CNTBP) into the easily fractured sites of [0°] 16 and [0°/90°] 4S composite laminates, and comparatively explores how the CNTBP affects the flexural properties of the laminates at 25, −15, and −55 °C.…”
mentioning
confidence: 99%